Health Education on Motivation of Health Cadres in High Risk Early Detection of Pregnant Women in Kepuh Village Boyolangu District, Tulungagung Regency - Erma Retnaningtyas; Retno Palupi Yonni Siwi (Science Midwifery, 2021)
Counseling on High Risk Early Detection (DDRT) can increase the motivation of Health Cadres to prevent complications and death in pregnant women. The purpose of this study was to determine the effect of health education on the motivation of cadres in early detection of high risk pregnant women in Kepuh Village, Boyolangu District, Tulungagung Regency. The design of this study was analytic as a pre-experiment, with the design of the One-group pre-post test design with a population of all posyandu cadres in the Village of Kepuh, Boyolangu Subdistrict, Tulungagung Regency with a total of 20 people. The sample is all from the population with a sampling technique in total sampling of 20 respondents. The collected data is processed by the Wilxocon test with a significance of α = 0.05. The results showed that most of the respondents were 11 (55.0%) respondents had moderate motivation before health education and most of the respondents were 14 (70.0%) respondents had strong motivation after health education. The results of the Wilxocon test obtained p-value = 0,000 for the influence of health education on the motivation of cadres in early detection of high risk pregnant women. Health education can increase the motivation of cadres in doing DDRT which ultimately can reduce the risk of emergency conditions for both the mother and the fetus.